Digital content marketing in business markets: Activities, consequences, and contingencies along the customer journey - Terho Harri; Mero Joel; Siutla Lotta; Jaakkola Elina (Elsevier Inc., 2022)
Fundamental shifts in business-to-business (B2B) buying behavior make digital content marketing (DCM) a strategic priority for vendors, though firms struggle to achieve its full potential, as a customer-centric marketing approach. To address important knowledge gaps in extant research, this study identifies key activities for realizing customer-centric DCM in B2B markets and key contingencies that influence its performance outcomes. A theories-in-use approach, building on 56 interviews with managers at 36 B2B companies that have invested heavily in DCM, advances current literature by developing an activity-based conceptualization, grounded in relevant marketing research streams (customer engagement, customer journey and marketing technology literature). The authors also empirically derive propositions about the key contingencies of DCM performance. This conceptualization and the related contingencies provide an actionable roadmap for effective implementation of DCM for managers in business markets.